Dorsally Comminuted Fractures of the Distal End of the Radius: Osteosynthesis with Volar Fixed Angle Locking Plates. (8th May 2013) - Gogna, Paritosh; Selhi, Harpal Singh; Singla, Rohit; Devgan, Ashish; Magu, Narender Kumar; Mahindra, Pankaj; Yamin, Mohammad
Abstract : Background . Dorsally comminuted distal radius fractures are unstable fractures and represent a treatment challenge. The objective of this study was to evaluate the functional and radiological outcome of dorsally comminuted fractures of the distal radius fixed with a volar locking plate. Patients and Methods . Thirty-three consecutive patients with dorsally comminuted fractures of the distal end of the radius were treated by open reduction and internal fixation with AO 2.4 mm (n = 19 )/3.5 mm (n = 14 ) volar locking distal radius plate (Synthes, Switzerland, marketed by Synthes India Pvt. Ltd.). There were 7 type A3, 8 type C2, and 18 type C3 fractures. The patients were followed up at 6 weeks, 3 months, 6 months, and 1 year postoperatively. Subjective assessment was done as per Disabilities Arm, Shoulder, and Hand (DASH) questionnaire. Functional evaluation was done by measuring grip strength and range of motion around the wrist; the radiological determinants were radial angle, radial length, volar angle, and ulnar variance. The final assessment was done as per Demerit point system of Saito. Results . There were 23 males and 10 females with an average age of 44.12 ± 18.63 years (18–61 years). Clinicoradiological consolidation of the fracture was observed in all cases at a mean of 9.6 weeks (range 7–12 weeks). The average final extension was 58.15° ± 7.83°, flexion was 54.62° ± 11.23°, supination was 84.23° ± 6.02°, and pronation was 80.92° ± 5.54°. Demerit point system of Saito yielded excellent results in 79% (n = 26 ), good in 18% (n = 6 ), and fair in 3% (n = 1 ) patients. Three patients had loss of reduction but none of the patients had tendon irritation or ruptures, implant failure, or nonunion at the end of an one-year followup. Conclusion . Volar locking plate fixation for dorsally comminuted distal radius fractures results in good to excellent functional outcomes despite a high incidence of loss of reduction and fracture collapse.